Spraying-free material capable of storing heat and preparation method thereof
By mixing the phase -changing medium and the degradable polymer material, combined with pearl powder, preparing a composite phase change material, solving the problem of lack of heat -storage function for existing spray -free materials, and realizing the function of efficient heat storage and heat dissipation. Solved the problem of heat energy.
Patent Information
- Application Number
- CN202411488405.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-01-24
AI Technical Summary
The existing spray-free materials lack heat storage function and cannot effectively solve the problem of heat waste.
By mixing phase change media and degradable polymer materials, combined with pearlescent powder, composite phase change materials are prepared to achieve heat storage that absorbs heat and releases heat.
It realizes the efficient heat storage and heat release functions of the material, solves the problem of thermal energy waste, and maintains good leakage prevention capabilities and heat storage efficiency.
Smart Images

Figure CN119350823A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of spray-free materials, and more particularly to a heat-storage spray-free material and a preparation method thereof. Background Art
[0002] Spray-free materials are innovative materials modified by special technology. They do not require traditional spraying technology and can be directly injected into the mold to show a bright appearance comparable to that of spray paint. This material not only simplifies the production process and improves efficiency, but also significantly reduces environmental pollution and achieves the goal of green production. As people pay more and more attention to environmental issues, spray-free materials with special effects are gradually showing their unique competitiveness. Spray-free aesthetic resins can perfectly replicate the colorful and bright tones and special effects such as pearlescent, glittering effects, metallic luster and texture produced by spray painting, thereby meeting the diverse and differentiated needs of customers. In addition, they can truly achieve energy conservation and emission reduction and reduce energy consumption during the production process. They can be widely used in crafts, toys, automobiles, home appliances, sporting goods, electronic products and office supplies.
[0003] Although spray-free parts have greater advantages than painted parts, the functionality of existing spray-free materials is still too single and the scope of application is relatively narrow. In response to this, patent CN110819063A discloses a high-performance antibacterial spray-free POM composite material and its preparation method, which achieves the broad-spectrum antibacterial effect of spray-free materials. Patent CN112778736A further gives the spray-free material an anti-fingerprint effect on the basis of antibacterial. Patent CN110804273A has developed a scratch-resistant and anti-fingerprint spray-free POM composite material. Patent CN116640382A discloses a spray-free material with excellent photosensitive color change and weather resistance under long-term illumination. However, there is currently no relevant research on spray-free materials with heat storage function in the prior art.
[0004] Therefore, developing a heat storage and spray-free material is an urgent problem to be solved by technicians in this field. Summary of the invention
[0005] In view of this, the present invention provides a heat storage spray-free material and a preparation method thereof, which utilizes phase change medium and degradable polymer to prepare a composite phase change material to achieve heat storage by absorbing and releasing heat, thereby solving the problem of heat energy waste.
[0006] In order to achieve the above object, the present invention adopts the following technical solution:
[0007] Firstly, the present invention provides a heat storage spray-free material, which comprises the following raw materials in parts by weight: 45-55 parts of phase change medium, 45-55 parts of degradable polymer material, and 1-5 parts of pearlescent powder.
[0008] The phase change medium is any one of polyolefin elastomer, high-density polyethylene and acrylonitrile-styrene-butadiene copolymer.
[0009] The degradable polymer material is any one of polylactic acid, polybutylene succinate, polybutylene adipate-terephthalate and polycaprolactone.
[0010] Polylactic acid is preferred.
[0011] The pearlescent powder is any one of sparkling pearl COA-KC163 pearlescent powder, pearl platinum COA-KC205 pearlescent powder, silvery white satin COA-KC108 pearlescent powder, sun gold KC-63309 pearlescent powder, bright gold KC-320 pearlescent powder, KC-3111 pearlescent powder, ZP7110 pearlescent powder, PE1201 pearlescent powder, and PE2001 pearlescent powder.
[0012] In addition, the present invention also provides a method for preparing the above-mentioned heat storage spray-free material, which specifically comprises the following steps:
[0013] S1, weigh the required raw materials according to the raw material ratio and mix them evenly;
[0014] S2, putting the mixed raw materials into a preheated internal mixer for rubber mixing to obtain a heat storage and spray-free material.
[0015] The preheating temperature of the internal mixer in step S2 is 200°C.
[0016] The temperature of the rubber mixing in step S2 is 200° C., the speed is 40 r / min, and the time is 20 min.
[0017] Compared with the prior art, the present invention discloses a heat storage spray-free material and a preparation method thereof, which uses a degradable polymer material and a phase change medium to mix, and adds pearlescent powder to prepare a heat storage spray-free material. Among them, the phase change medium will undergo a solid-liquid phase change conversion within the corresponding temperature range, and the degradable polymer material can play a supporting role, ensuring that the prepared product will not melt while achieving the heat storage effect of absorbing / releasing heat.
[0018] The test of differential scanning calorimeter shows that the relative enthalpy efficiency of the material prepared in the present invention is above 40%, indicating that the prepared material has a relatively excellent heat storage capacity.
[0019] The leakage test shows that the material prepared in the present invention does not substantially deform after being treated at 150° C. for a long time, indicating that the material prepared in the present invention has good anti-leakage capability.
[0020] The heat storage spray-free material prepared by the present invention has the heat storage function of absorbing / releasing heat, can solve the problem of heat energy waste, can make efficient use of heat energy in the spray-free field, and has the advantages of energy storage / conversion / use. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.
[0022] Figure 1 SEM images of POE / PLA-based heat storage spray-free materials, where a is Example 1, b is Example 2, c is Example 3, d is Comparative Example 1, e is Comparative Example 4, and f is Comparative Example 7
[0023] Figure 2 SEM images of HDPE / PLA-based heat storage spray-free materials, where a is Example 4, b is Example 5, c is Example 6, d is Comparative Example 2, e is Comparative Example 5, and f is Comparative Example 7
[0024] Figure 3 SEM images of ABS / PLA-based heat storage spray-free materials, where a is Example 7, b is Example 8, c is Example 9, d is Comparative Example 3, e is Comparative Example 6, and f is Comparative Example 7
[0025] Figure 4 The leakage test results of each embodiment group are shown in FIG.
[0026] Figure 5 Leakage test results for each comparative example group DETAILED DESCRIPTION
[0027] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0028] Example 1
[0029] (1) Weigh and mix the raw materials according to the weight ratio of polyolefin elastomer (POE), polylactic acid (PLA), and sparkling pearl COA-KC163 pearl powder of 50:50:1.
[0030] (2) Preheat the internal mixer to 200°C, add the mixed raw materials, and start mixing rubber. The mixing temperature is 200°C, the speed is 40r / min, and the time is 20min. After the mixing is completed, the heat storage POE-based spray-free material is obtained.
[0031] Example 2
[0032] (1) Weigh and mix the raw materials according to the weight ratio of POE, PLA, and pearl platinum COA-KC205 pearlescent powder of 50:50:2.
[0033] (2) Preheat the internal mixer to 200°C, add the mixed raw materials, and start mixing rubber. The mixing temperature is 200°C, the speed is 40r / min, and the time is 20min. After the mixing is completed, the heat storage POE-based spray-free material is obtained.
[0034] Example 3
[0035] (1) Weigh and mix the raw materials according to the weight ratio of POE, PLA and silver fine satin COA-KC108 pearlescent powder of 50:50:1.
[0036] (2) Preheat the internal mixer to 200°C, add the mixed raw materials, and start mixing rubber. The mixing temperature is 200°C, the speed is 40r / min, and the time is 20min. After the mixing is completed, the heat storage POE-based spray-free material is obtained.
[0037] Example 4
[0038] (1) Weigh and mix high-density polyethylene (HDPE), polylactic acid (PLA), and Sun Gold KC-63309 pearlescent powder in a weight ratio of 50:50:1.
[0039] (2) Preheat the internal mixer to 200°C, add the mixed raw materials, and start mixing rubber. The mixing temperature is 200°C, the speed is 40r / min, and the time is 20min. After the mixing is completed, the heat storage POE-based spray-free material is obtained.
[0040] Example 5
[0041] (1) Weigh and mix the raw materials according to the weight ratio of HDPE, PLA and bright gold KC-320 pearlescent powder of 50:50:2.
[0042] (2) Preheat the internal mixer to 200°C, add the mixed raw materials, and start mixing rubber. The mixing temperature is 200°C, the speed is 40r / min, and the time is 20min. After the mixing is completed, the heat storage POE-based spray-free material is obtained.
[0043] Example 6
[0044] (1) Weigh and mix the raw materials according to the weight ratio of HDPE, PLA and KC-3111 pearlescent powder of 50:50:1.
[0045] (2) Preheat the internal mixer to 200°C, add the mixed raw materials, and start mixing rubber. The mixing temperature is 200°C, the speed is 40r / min, and the time is 20min. After the mixing is completed, the heat storage POE-based spray-free material is obtained.
[0046] Example 7
[0047] (1) Weigh and mix acrylonitrile-butadiene-styrene copolymer (ABS), polylactic acid (PLA), and ZP7110 pearlescent powder in a weight ratio of 50:50:1.
[0048] (2) Preheat the internal mixer to 200°C, add the mixed raw materials, and start mixing rubber. The mixing temperature is 200°C, the speed is 40r / min, and the time is 20min. After the mixing is completed, the heat storage POE-based spray-free material is obtained.
[0049] Example 8
[0050] (1) Weigh and mix the raw materials according to the weight ratio of ABS, PLA and PE1201 pearl powder of 50:50:2.
[0051] (2) Preheat the internal mixer to 200°C, add the mixed raw materials, and start mixing rubber. The mixing temperature is 200°C, the speed is 40r / min, and the time is 20min. After the mixing is completed, the heat storage POE-based spray-free material is obtained.
[0052] Example 9
[0053] (1) Weigh and mix the raw materials according to the weight ratio of ABS, PLA and PE2001 pearl powder of 50:50:1.
[0054] (2) Preheat the internal mixer to 200°C, add the mixed raw materials, and start mixing rubber. The mixing temperature is 200°C, the speed is 40r / min, and the time is 20min. After the mixing is completed, the heat storage POE-based spray-free material is obtained.
[0055] Comparative Example 1
[0056] (1) Weigh and mix the raw materials according to the weight ratio of POE and PLA of 50:50.
[0057] (2) Preheat the internal mixer to 200°C, add the mixed raw materials, and start mixing rubber. The mixing temperature is 200°C, the speed is 40r / min, and the time is 20min. After the mixing is completed, the heat storage POE-based spray-free material is obtained.
[0058] Comparative Example 2
[0059] (1) Weigh and mix the raw materials according to the weight ratio of HDPE and PLA of 50:50.
[0060] (2) Preheat the internal mixer to 200°C, add the mixed raw materials, and start mixing rubber. The mixing temperature is 200°C, the speed is 40r / min, and the time is 20min. After the mixing is completed, the heat storage POE-based spray-free material is obtained.
[0061] Comparative Example 3
[0062] (1) Weigh and mix the raw materials according to the weight ratio of ABS and PLA of 50:50.
[0063] (2) Preheat the internal mixer to 200°C, add the mixed raw materials, and start mixing rubber. The mixing temperature is 200°C, the speed is 40r / min, and the time is 20min. After the mixing is completed, the heat storage POE-based spray-free material is obtained.
[0064] Comparative Example 4
[0065] Preheat the internal mixer to 200°C, add only POE, and start mixing rubber. The mixing temperature is 200°C, the speed is 40r / min, and the time is 20min. After the mixing is completed, the POE material is obtained.
[0066] Comparative Example 5
[0067] Preheat the internal mixer to 200°C, add only HDPE, and start mixing rubber. The mixing temperature is 200°C, the speed is 40r / min, and the time is 20min. After the mixing is completed, the HDPE material is obtained.
[0068] Comparative Example 6
[0069] Preheat the internal mixer to 200°C, add only ABS and start mixing rubber. The mixing temperature is 200°C, the speed is 40r / min, and the time is 20min. After the mixing is completed, the ABS material is obtained.
[0070] Comparative Example 7
[0071] Preheat the internal mixer to 200°C, add only PLA, and start mixing rubber. The mixing temperature is 200°C, the speed is 40r / min, and the time is 20min. After the mixing is completed, the PLA material is obtained.
[0072] SEM characterization
[0073] The microstructure of each embodiment and comparative example was characterized by scanning electron microscopy. Figure 1-3As can be seen from the picture, when the phase change medium and the degradable polymer material are mixed, the microstructure of the product is a lamellar structure, while when the two are used alone, there is no such structure. This is because when the two are mixed, the polymer material plays the role of a supporting material, while polylactic acid plays the role of a phase change medium.
[0074] Thermal storage performance test
[0075] The temperature variation of the materials prepared in the examples and comparative examples was tested by differential scanning calorimetry (DSC), the test temperature range was 30-150°C, the temperature rise and fall rate was 10°C / min, and the ambient atmosphere was nitrogen. The results are shown in the following table:
[0076]
[0077] According to the data in the table, comparative example 4 is POE, and its crystallization enthalpy value is 122.8 J / g, and comparative example 5 is HDPE, and its crystallization enthalpy value is 176.46 J / g. Comparative example 1 is a combination of 50% POE + 50% PLA, and its crystallization enthalpy value is 64.65 J / g, and the relative enthalpy efficiency is 51.50%. Comparative example 2 is a combination of 50% HDPE + 50% PLA, and its crystallization enthalpy value is 88.98 J / g, and the relative enthalpy efficiency is 50.00%. Based on comparative example 1, different weights and different types of pearl powder were added to examples 1-3, and the crystallization enthalpy values were further reduced, which were 57.75 J / g, 59.43 J / g and 55.74 J / g, respectively, and the relative enthalpy efficiencies were 46.20%, 48.20% and 44.30%, respectively. Based on Comparative Example 2, different weights and types of pearl powder were added to Examples 4-6, and the crystallization enthalpy values were further reduced, which were 82.94 J / g, 83.85 J / g and 77.60 J / g, respectively, and the relative enthalpy efficiencies were 46.10%, 47.00% and 44.10%, respectively. The DSC results show that the phase change composite spray-free material composed of phase change medium and degradable polymer material has a high heat storage capacity and excellent thermal management performance, and can be widely used in various household appliances that may come into contact with human skin. After adding pearl powder, the relative enthalpy efficiency is still maintained at more than 44%, and it still has a good heat storage capacity.
[0078] Leak test
[0079] The materials prepared in the test examples and comparative examples were placed in an oven at 150°C for 6 hours, 12 hours, 18 hours and 24 hours to test their leakage. Figure 4 As can be seen from the figure, the material prepared in the embodiment of the present invention does not deform substantially after being treated at 150° C. for a long time, indicating that the material prepared in the present invention has good anti-leakage capability.
[0080] In this specification, each embodiment is described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the embodiments can be referred to each other. For the device disclosed in the embodiment, since it corresponds to the method disclosed in the embodiment, the description is relatively simple, and the relevant parts can be referred to the method part.
[0081] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A heat storage spray-free material, characterized in that: The raw material composition includes the following parts by weight: 45-55 parts of phase change medium, 45-55 parts of degradable polymer material and 1-5 parts of pearl powder.
2. The heat storage spray-free material according to claim 1, characterized in that: The phase change medium is any one of polyolefin elastomer, high-density polyethylene and acrylonitrile-styrene-butadiene copolymer.
3. The heat storage spray-free material according to claim 1, characterized in that: The degradable polymer material is any one of polylactic acid, polybutylene succinate, polybutylene adipate-terephthalate and polycaprolactone.
4. The heat storage spray-free material according to claim 3, characterized in that: The degradable polymer material is preferably polylactic acid.
5. The heat storage spray-free material according to claim 1, characterized in that: The pearlescent powder is any one of sparkling pearl COA-KC163 pearlescent powder, pearl platinum COA-KC205 pearlescent powder, silvery white satin COA-KC108 pearlescent powder, sun gold KC-63309 pearlescent powder, bright gold KC-320 pearlescent powder, KC-3111 pearlescent powder, ZP7110 pearlescent powder, PE1201 pearlescent powder, and PE2001 pearlescent powder.
6. A method for preparing the heat storage spray-free material according to any one of claims 1 to 5, characterized in that: The steps include: S1, weigh the required raw materials according to the raw material ratio and mix them evenly; S2, putting the mixed raw materials into a preheated internal mixer for rubber mixing to obtain a heat storage and spray-free material.
7. The method for preparing the heat storage spray-free material according to claim 6, characterized in that: The preheating temperature of the internal mixer in step S2 is 200°C.
8. The method for preparing the heat storage spray-free material according to claim 6, characterized in that: The temperature of the rubber mixing in step S2 is 200° C., the speed is 40 r / min, and the time is 20 min.
Citation Information
Patent Citations
Scratch-resistant anti-fingerprint spray-free POM composite material and preparation method thereof
CN110804273A
High-performance antibacterial spraying-free POM composite material and preparation method thereof
CN110819063A
Highly antibacterial and anti-fingerprint spraying-free polycarbonate alloy material and preparation method thereof
CN112778736A
Spraying-free material as well as preparation method and application thereof
CN116640382A